A high entropy positive electrode material for potassium ion batteries and its preparation method and application

By doping polymetallic elements into the positive electrode material of the potassium ion battery, a high-entropy layered oxide with a P2/rock salt biphasic symbiotic structure was prepared, which solved the structural degradation problem caused by phase transition in the high-voltage region, and achieved high structural stability and excellent electrochemical performance.

CN119495741BActive Publication Date: 2025-05-02HENAN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510072427.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-05-02
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The phase change of the existing potassium ion battery positive electrode material in the high-voltage region causes structural degradation, limiting the cyclic stability and capacity of the material.

Method used

By controlling the trace doping of polymetallic elements, a high-entropy layered oxide positive electrode material with a P2/rock salt biphasic symbiotic structure was prepared, and the biphasic symbiotic structure was used to relieve lattice stress and improve structural stability.

Benefits of technology

High structural stability and excellent rate performance are achieved, K+ reversible storage capacity and initial Coulomb efficiency are improved, and the cycle life of the material is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495741B_ABST
    Figure CN119495741B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-entropy cathode material for potassium ion batteries, a preparation method thereof, and an application thereof. The high-entropy cathode material is a layered oxide with a P2 / rock salt dual-phase coexisting structure, and its chemical general formula is K 0.6 Mn 0.75‑x Ni 0.1 Ti 0.1 Mg x Cu 0.05 O2, where 0 < x ≤ 0.1. The preparation process adopts the high-temperature solid-phase method. By regulating the types and contents of doped elements, a high-entropy layered oxide cathode material with two coexisting P2 / rock salt phase structures is finally formed. The introduction of a small amount of rock salt phase alleviates the sliding of the TM layer during charging and the large structural stress generated during cycling, improves the lattice distortion and crack generation inside the particles during long cycling, and thus significantly improves the electrochemical cycling stability and rate performance of potassium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode materials for potassium ion batteries, and in particular relates to a high-entropy positive electrode material for potassium ion batteries and a preparation method and application thereof. Background Art

[0002] With the increasing energy consumption in modern society, energy conservation is bound to become one of the focuses of today's development. Lithium-ion batteries (LIB) are widely used in electronic devices and automobiles. However, the scarcity of lithium resources is attracting attention. The same working mechanism as lithium-ion batteries (LIB), along with more abundant resource reserves and lower cost considerations, makes potassium-ion batteries (KIB) one of the ideal choices for new energy storage systems. In addition, the large ion radius of K + Reversible insertion / extraction in existing LIB anode materials such as graphite has been studied and confirmed, which greatly accelerates the practical application value of KIB. Therefore, it is necessary to explore structurally stable and high-energy cathode materials to accommodate large ionic radius K + Reversible intercalation reactions have become the focus of current research.

[0003] Among various cathode materials, K + Layered transition metal oxides (KxTMO2) have attracted great attention from researchers due to their high compactness and excellent volumetric energy density. + According to the occupation position and stacking order of O layers, layered oxides can be divided into P2, P3 and O3 structures. In these KxTMO2, due to the K + The triangular prism environment shared by two adjacent faces in the potassium layer directly favors K due to its lower energy barrier. + The P2 structure seems to be a more promising candidate material for a long cycle life cathode due to its low K content. However, the lower K content in the P2 phase limits the capacity, and the phase transition of the P2 phase in the high voltage region causes a large volume change, which leads to a huge volume change and structural degradation of the material, ultimately resulting in rapid capacity and voltage decay, limiting practical applications.

[0004] In order to solve this problem, the purpose of improving the material cycle stability can be achieved by constructing a composite material structure and introducing other elements by doping. The composite structure has a structural constraint effect, and the mutual constraints between adjacent structures inhibit harmful phase changes. The high entropy compounds formed by doping with multiple ions can combine the advantages of each element, thereby improving the electrochemical performance of the positive electrode material. Summary of the invention

[0005] The technical problem solved by the present invention is to provide a high-entropy positive electrode material for a potassium ion battery and a preparation method thereof. The method controls the ratio and composition of doped ions to prepare a layered oxide with a P2 / rock salt dual-phase symbiotic structure with high structural stability and excellent rate performance. The prepared layered oxide can be used as a positive electrode material for a potassium ion battery for assembling a potassium ion battery.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] In the first aspect, the present invention provides a high entropy cathode material for a potassium ion battery, wherein the high entropy cathode material is a layered oxide having a P2 / rock salt dual-phase symbiotic structure, and its general chemical formula is K 0.6 Mn 0.75-x Ni 0.1 Ti 0.1 Mg x Cu 0.05 O2, where 0<x≤0.1.

[0008] In a second aspect, the present invention provides a method for preparing a high entropy cathode material for a potassium ion battery, the specific steps of which are:

[0009] Step S1: According to the chemical formula K 0.6 Mn 0.75-x Ni 0.1 Ti 0.1 Mg x Cu 0.05 The molar ratio of each element in O2 is respectively weighed, potassium source, manganese source, nickel source, magnesium source, titanium source and copper source, and mixed, and then an organic solvent is added to perform ball milling and mixing to obtain a precursor slurry;

[0010] Step S2: drying the precursor powder obtained in step S1, pressing the precursor powder into tablets, calcining the tablets at 800-1000° C., and cooling the precursor powder to obtain a layered oxide having a P2 / rock salt dual-phase symbiotic structure, i.e., a high-entropy cathode material for potassium ion batteries.

[0011] It is further defined that in step S1, the potassium source is potassium carbonate, the manganese source is manganese dioxide, the nickel source is nickel oxide, the magnesium source is magnesium oxide, the titanium source is titanium dioxide, and the copper source is copper oxide.

[0012] It is further defined that in step S1, the ball milling speed is 400-600 rpm, the ball milling time is 8-12 h, the ball milling beads are agate beads, and the mass ratio of the ball milling beads to the mixed slurry is 10-15:1.

[0013] It is further defined that in step S1, the organic solvent is ethanol.

[0014] It is further defined that in step S2, the drying temperature is 60-80°C and the drying time is 1-3 hours.

[0015] It is further defined that in step S2, the precursor powder is pressed into a disc at a pressure of 10-20 MPa before calcination.

[0016] It is further defined that in step S2, the precursor powder is pressed into a tablet and then calcined in an air atmosphere. The heating rate of the calcination process is 2-5°C / min, and the calcination time is 10-15h. After calcination, the powder is cooled to 200°C and transferred to a glove box filled with argon. After cooling to room temperature, a layered oxide with a P2 / rock salt dual-phase symbiotic structure, i.e., a high-entropy positive electrode material for potassium ion batteries, is obtained.

[0017] In a third aspect, the present invention provides a positive electrode sheet for a potassium ion battery, the positive electrode sheet comprising an aluminum foil and a coating layer coated on the aluminum foil, wherein the coating layer is a mixture of SP conductive carbon black, a PVDF binder, and a layered oxide having a P2 / rock salt dual-phase symbiotic structure. The specific preparation process of the positive electrode sheet for a potassium ion battery is as follows: the layered oxide having a P2 / rock salt dual-phase symbiotic structure, SP conductive carbon black, and a PVDF binder are uniformly mixed in N-methylpyrrolidone in a mass ratio of 7:2:1 to obtain a mixture; and then the mixture is coated on an aluminum foil and vacuum dried to obtain a positive electrode sheet for a potassium ion battery.

[0018] In a fourth aspect, the present invention provides a potassium ion battery, using the above-mentioned potassium ion battery positive electrode sheet as the positive electrode and metallic potassium as the negative electrode, the electrolyte comprising a solute and an organic solvent, wherein the solute is potassium hexafluorophosphate, and the organic solvent is one or more of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC) and fluoroethylene carbonate (FEC), and the concentration of the solute in the electrolyte is 0.8~1 mol / L.

[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0020] 1. The dual-phase symbiotic structure formed after trace doping of multiple metal elements in the present invention effectively alleviates the accumulation of lattice stress during the cycle, mainly due to the pinning structure formed at the interface of the P2 phase and the rock salt phase, which reduces the sliding of the transition metal layer, thereby providing high structural stability close to zero strain.

[0021] 2. The dual-phase symbiotic structure formed by trace doping of multi-metal elements in the present invention can improve K to a certain extent. + Reversible storage capability with higher initial Coulombic efficiency.

[0022] 3. The dual-phase symbiotic structure formed by trace doping of multi-metal elements in the present invention not only alleviates the 3+ The Jahn-Teller effect brought about by this change not only changes the local electronic environment around O, but also weakens the interaction between K and O, thereby expanding the K layer spacing and accelerating the K+ The transmission speed makes the dual-phase material have good rate performance and cycle performance.

[0023] 4. The raw materials for the preparation of the material of the present invention are abundant, and the synthesis method is simple, safe and green. It does not require complicated processing procedures and high-end instruments, has low cost, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD pattern of the positive electrode material prepared in Example 1.

[0025] Figure 2 The SEM image (left) and TEM image (right) of the positive electrode material prepared in Example 1.

[0026] Figure 3 This is a charge and discharge curve diagram of the positive electrode material prepared in Example 1 at a current density of 20 mA / g.

[0027] Figure 4 This is the XRD pattern of the positive electrode material prepared in Comparative Example 1.

[0028] Figure 5 The SEM image (left) and TEM image (right) of the positive electrode material prepared in Comparative Example 1.

[0029] Figure 6 This is a charge and discharge curve diagram of the positive electrode material prepared in Comparative Example 1.

[0030] Figure 7 This is the XRD pattern of the positive electrode material prepared in Comparative Example 2.

[0031] Figure 8 The SEM image (left) and TEM image (right) of the positive electrode material prepared in Comparative Example 2.

[0032] Fig. 9 This is the charge and discharge curve of the positive electrode material prepared in Comparative Example 2.

[0033] Fig.10 The positive electrode materials prepared in Example 1 and Comparative Example 1 and Comparative Example 2 were -1 Comparison of cycling performance under different current densities.

[0034] Fig.11 This is a comparison chart of the rate performance of the positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2 at different current densities. DETAILED DESCRIPTION

[0035] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Example 1

[0036] High-entropy layered oxide cathode material K for potassium ion batteries with P2 / rock salt dual-phase symbiotic structure 0.6 Mn 0.7 Ni 0.1 Mg 0.05 Cu 0.05 Ti 0.1 Preparation of O2:

[0037] Step S1: According to K 0.6 Mn 0.7 Ni 0.1 Mg 0.05 Cu 0.05 Ti 0.1 Potassium carbonate, nickel oxide, manganese dioxide, magnesium oxide, copper oxide and titanium dioxide were weighed and mixed in a stoichiometric ratio of O2, and then placed in a ball mill and anhydrous ethanol was added as a solvent. The ball mill speed was set to 500 rpm, the ball milling time was 9 hours, agate beads were used for the ball milling beads, and the mass ratio of the ball milling beads to the mixed slurry was 10:1; potassium carbonate was used in excess of 5wt.% to make up for the loss during high-temperature calcination; the mixed slurry was placed in a blast drying oven and dried at 60°C for 2 hours to obtain a precursor powder;

[0038] Step S2: The obtained precursor powder is pressed into a disc, placed in a muffle furnace, and calcined at high temperature in an air atmosphere. The calcination process is heated to 1000°C at a heating rate of 5°C / min and kept at this temperature for 15 hours; then cooled to 200°C and quickly transferred to a glove box filled with argon gas, and further cooled to room temperature to obtain a high entropy layered oxide potassium ion battery positive electrode material K with a P2 / rock salt dual-phase symbiotic structure. 0.6 Mn 0.7 Ni 0.1 Mg 0.05 Cu 0.05 Ti 0.1 O2.

[0039] High entropy layered oxide potassium ion battery cathode material K 0.6 Mn 0.7 Ni 0.1 Mg 0.05 Cu 0.05 Ti 0.1 O2, Super P and PVDF binder were mixed in a mass ratio of 7:2:1, and a certain amount of solvent N-methylpyrrolidone was added. After slurrying in a mortar, it was coated on aluminum foil and dried in a vacuum oven at 80°C for 12 hours to obtain a K-containing 0.6 Mn 0.7 Ni 0.1 Mg 0.05 Cu 0.05 Ti 0.1The prepared potassium ion battery positive electrode and the metal potassium negative electrode are assembled into a potassium ion battery, GF / D is used as the battery separator, and the electrolyte is 0.8 mol L −1 KPF6 in diethyl carbonate (DEC) / ethylene carbonate (EC) (volume ratio 1:1) solution. CR2032 batteries were used for the electrochemical performance test. The battery assembly was carried out in a glove box filled with argon atmosphere, and the water and oxygen concentrations were both less than 0.1ppm.

[0040] Figure 1 This is the X-ray diffraction diagram of the positive electrode material prepared in Example 1. It can be seen from the figure that the P2 phase accounts for 91.1% of the dual-phase high-entropy transition metal layered oxide prepared in this example, and the rock salt phase accounts for 8.9%. Figure 2 Field emission scanning electron microscopy and high-resolution transmission electron microscopy images show that the dual-phase high-entropy transition metal layered oxide prepared in Example 1 is composed of irregular blocky particles with uneven sizes, and the particle size distribution is 2-8 μm; at the same time, high-resolution transmission electron microscopy can observe two different lattice fringes, and the spacing between adjacent crystal planes is 0.64 nm and 0.21 nm, respectively, belonging to the (002) crystal plane of the P2 phase and the (200) crystal plane of the rock salt phase. Figure 3 It can be seen that the positive electrode material prepared in this example has a discharge specific capacity of 110 mAh / g at a current density of 20 mA / g within a voltage range of 1.5-4 V. Fig.10 This is a comparison chart of the cycle performance of the positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2 at a current density of 20 mA / g. It can be seen from the figure that the capacity retention rate of the positive electrode material prepared in Example 1 after 100 cycles is 89%, which is much higher than that of Comparative Examples 1 and 2. Fig.11 The figure is a comparison chart of the rate performance of the positive electrode materials prepared in Example 1 and Comparative Examples 1 and 2 at different current densities. It can be seen from the figure that the positive electrode material prepared in Example 1 still has a discharge specific capacity of 79 mAh / g at a current density of 500 mA / g.

[0041] Comparative Example 1

[0042] Pure P2 phase structure of high entropy layered oxide cathode material for potassium ion batteries 0.6 Mn 0.73 Ni 0.1 Mg 0.02 Cu 0.05 Ti 0. Preparation of 1O2:

[0043] The preparation method is the same as that in Example 1, except that the raw materials are divided into 0.6 Mn 0.73 Ni 0.1 Mg0.02 Cu 0.05 Ti 0.1 O2 was added in a stoichiometric ratio.

[0044] The prepared positive electrode material was subjected to structural characterization and electrochemical performance testing in the same manner as in Example 1.

[0045] Figure 4 This is the XRD diagram of the positive electrode material obtained in Comparative Example 1. It can be seen from the figure that the positive electrode material prepared in Comparative Example 1 has good crystallinity and a pure P2 phase structure with a space group of P63 / mmc. Figure 5 Field emission scanning electron microscopy and high-resolution transmission electron microscopy images of the positive electrode material of pure P2 phase structure prepared in Comparative Example 1. It can be seen from the figure that the pure P2 phase high entropy transition metal oxide prepared in Comparative Example 1 has a similar morphology to Example 1, with an average particle size of 2-10 μm; high-resolution transmission electron microscopy confirms that the material only contains a layered structure, and the spacing between the crystal planes is measured to be 0.64 nm, corresponding to the (002) plane of the P2 phase layered oxide; Figure 6 It can be seen that the positive electrode material prepared in Comparative Example 1 has a charge and discharge curve at a current density of 20 mA / g in the voltage range of 1.5~4 V, and its first cycle discharge capacity is 115 mAh / g, which is slightly higher than that in Example 1. This is because the rock salt phase exists as an inert phase inside the structure, and the presence of a small part of the rock salt phase will sacrifice a small part of the discharge capacity. The capacity retention rate of the positive electrode material prepared in Comparative Example 1 after 100 cycles is 73.5%, and the structural stability is slightly worse than that of the dual-phase high-entropy positive electrode material, but better than that of the dual-phase low-entropy positive electrode material prepared in Comparative Example 2, and the discharge capacity is 59 mAh / g at a current density of 500 mA / g.

[0046] Comparative Example 2

[0047] Low-entropy layered oxide cathode material K for potassium ion batteries with P2 / rock salt symbiotic structure 0.6 Mn 0.8 Ni 0.2 Preparation of O2:

[0048] Step S1: According to K 0.6 Mn 0.8 Ni 0.2 Potassium carbonate, nickel oxide and manganese dioxide were weighed and mixed in a stoichiometric ratio of O2, and then placed in a ball mill and anhydrous ethanol was added as a solvent. The ball mill speed was set to 500 rpm, the ball milling time was 9 h, agate beads were used for the ball milling beads, and the mass ratio of the ball milling beads to the mixed slurry was 10:1; potassium carbonate was used in excess of 5wt.% to make up for the loss during the high-temperature calcination process; the mixed slurry was placed in a blast drying oven and dried at 60°C for 2 h to obtain a precursor powder;

[0049] Step S2: The obtained precursor powder is pressed into a disc, placed in a muffle furnace for high-temperature calcination in an air atmosphere, and the temperature is increased to 1000°C at a heating rate of 5°C / min and kept at this temperature for 15 hours; then cooled to 200°C and quickly transferred to a glove box filled with argon gas, and further cooled to room temperature to obtain a low-entropy layered oxide potassium ion battery positive electrode material K with a P2 / rock salt dual-phase symbiotic structure. 0.6 Mn 0.8. Ni 0.2 O2.

[0050] The prepared P2 / rock salt dual-phase low entropy layered oxide potassium ion battery positive electrode material K without any trace element doping was prepared in the same manner as in Example 1. 0.6 Mn 0.8. Ni 0.2 O2 was used for structural characterization and electrochemical performance testing.

[0051] Figure 7 This is the XRD diagram of the positive electrode material prepared in Comparative Example 2. It can be seen from the figure that the P2 phase positive electrode material containing the rock salt phase can be synthesized without doping any ions. Figure 8 The field emission scanning electron microscope and high-resolution transmission electron microscope images of the positive electrode material prepared in Comparative Example 2 show that the morphology of the positive electrode material prepared in Comparative Example 2 is different from that in Example 1 and Comparative Example 1. When no ions are doped, the particle size of the material is relatively uniform, with a particle size of 500nm~6μm; the measured spacing of the (002) crystal plane of the P2 phase is 0.63nm. The lattice spacing of the HE-P2 / rock salt dual-phase material is wider than that of LE-P2 / O3, which is more conducive to K + diffusion. Fig. 9 This is the charge and discharge curve of the positive electrode material prepared in Comparative Example 2 in the voltage range of 1.5~4V. It can be seen from the figure that the first cycle discharge capacity is 100mAh / g, the capacity retention rate is 55.6% after 100 cycles, and the discharge capacity is 40mAh / g at a current density of 500mA / g. Its cycle performance and rate performance are far inferior to those of high-entropy positive electrode materials.

[0052] Table 1 is a comparison of the electrochemical performance data of button cells of positive electrode sheets prepared from samples obtained in Example 1 and Comparative Examples 1-2 as positive electrode materials for potassium ion batteries:

[0053] sample <![CDATA[Reversible specific capacity (mAh g −1 ).]]> Initial coulombic efficiency (%) <![CDATA[Capacity retention rate after 100 cycles / % (20 mA g −1 ).]]> <![CDATA[500mA g −1 Specific capacity at rate (mAh g −1 )]]> Example 1 120 63 89 79 Comparative Example 1 110 62 73.5 59 Comparative Example 2 100 49 55.6 40

[0054] By comparing the electrochemical performances of Example 1, Comparative Example 1, and Comparative Example 2, it can be seen that the positive electrode material prepared in Example 1 has the best cycle performance and rate performance. 2+The doping content of P2 and rock salt is used to construct a two-phase material with interlaced growth. The prepared composite structure positive electrode material can resist the irreversible phase change caused by structural collapse during the cycle, relieve stress accumulation, and enhance the matrix K 0.6 Mn 0.8 Ni 0.2 The crystal stability of O2 materials is improved, thereby improving the cycle stability. At the same time, the presence of a small amount of rock salt phase helps to improve the interface conductivity and accelerate the K + The transmission speed makes the dual-phase cathode material have good rate performance. Therefore, the dual-phase high-entropy cathode material formed by multi-element co-doping in the present invention can improve the electrochemical properties of potassium ion battery electrode materials in many aspects, and the prepared high-entropy layered oxide exhibits excellent electrochemical properties.

[0055] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A high entropy cathode material for a potassium ion battery, characterized in that: The high entropy cathode material is a layered oxide with a P2 / rock salt dual-phase symbiotic structure, and its general chemical formula is K 0.6 Mn 0.75-x Ni 0.1 Ti 0.1 Mg x Cu 0.05 O2, where x=0.

05.

2. The method for preparing a high entropy cathode material for a potassium ion battery according to claim 1, characterized in that The specific steps are: Step S1: According to the chemical formula K 0.6 Mn 0.75-x Ni 0.1 Ti 0.1 Mg x Cu 0.05 The molar ratio of each element in O2 is respectively weighed, potassium source, manganese source, nickel source, magnesium source, titanium source and copper source are mixed, and then an organic solvent is added to perform ball milling and mixing to obtain a precursor slurry, and the precursor slurry is dried to obtain a precursor powder; Step S2: drying the precursor powder obtained in step S1, pressing the precursor powder into tablets, calcining the tablets at 800-1000° C., and cooling the precursor powder to obtain a layered oxide having a P2 / rock salt dual-phase symbiotic structure, i.e., a high-entropy cathode material for potassium ion batteries.

3. The method for preparing a high entropy cathode material for a potassium ion battery according to claim 2, wherein: In step S1, the potassium source is potassium carbonate, the manganese source is manganese dioxide, the nickel source is nickel oxide, the magnesium source is magnesium oxide, the titanium source is titanium dioxide, and the copper source is copper oxide.

4. The method for preparing a high entropy cathode material for a potassium ion battery according to claim 2, wherein: In step S1, the ball milling speed is 400-600 rpm, the ball milling time is 8-12 h, the ball milling beads are agate beads, and the mass ratio of the ball milling beads to the mixed slurry is 10-15:

1.

5. The method for preparing a high entropy cathode material for a potassium ion battery according to claim 2, wherein: In step S1, the organic solvent is ethanol.

6. The method for preparing a high entropy cathode material for a potassium ion battery according to claim 2, wherein: In step S2, the drying temperature is 60-80°C, the drying time is 1-3 hours, and the precursor powder is pressed into a disc at a pressure of 10-20 MPa before calcination.

7. The method for preparing a high entropy cathode material for a potassium ion battery according to claim 2, wherein: In step S2, the precursor powder is pressed into a tablet and then calcined in an air atmosphere. The heating rate of the calcination process is 2-5°C / min and the calcination time is 10-15h. After calcination, the powder is cooled to 200°C and transferred to a glove box filled with argon gas. After cooling to room temperature, a layered oxide with a P2 / rock salt dual-phase symbiotic structure, i.e., a high-entropy positive electrode material for potassium ion batteries, is obtained.

8. A positive electrode sheet for a potassium ion battery, characterized in that: The positive electrode sheet comprises an aluminum foil and a coating layer coated on the aluminum foil, wherein the coating layer is a mixture of SP conductive carbon black, PVDF binder and the layered oxide with a P2 / rock salt dual-phase symbiotic structure as claimed in claim 1.

9. The method for preparing a positive electrode sheet for a potassium ion battery according to claim 8, characterized in that The specific steps are: mixing a layered oxide with a P2 / rock salt dual-phase symbiotic structure, SP conductive carbon black and a PVDF binder in a mass ratio of 7:2:1 in N-methylpyrrolidone to obtain a mixture; then coating the mixture on an aluminum foil and vacuum drying it to obtain a potassium ion battery positive electrode sheet.

10. A potassium ion battery, characterized in that: The potassium ion battery positive electrode sheet according to claim 8 is used as the positive electrode, and metallic potassium is used as the negative electrode. The electrolyte comprises a solute and an organic solvent, wherein the solute is potassium hexafluorophosphate, and the organic solvent is one or more of propylene carbonate, ethylene carbonate, diethyl carbonate and fluoroethylene carbonate, and the concentration of the solute in the electrolyte is 0.8~1 mol / L.

Citation Information

Patent Citations

  • Bismuth-tin-antimony-containing high-entropy oxide negative electrode energy storage material as well as preparation method and application thereof

    CN114530590A

  • Preparation method of high-entropy oxide positive electrode material of potassium ion battery

    CN115872462A